Correction: Dependence of the Ce(iii)/Ce(iv) ratio on intracellular localization in ceria nanoparticles internalized by human cells. Issue 15 (5th April 2017) - Ferraro, Daniela; Tredici, Ilenia G.; Ghigna, Paolo; Castillo-Michel, Hiram; Falqui, Andrea; Di Benedetto, Cristiano; Alberti, Giancarla; Ricci, Vittorio; Anselmi-Tamburini, Umberto; Sommi, Patrizia
Abstract : Correction for 'Dependence of the Ce(iii )/Ce(iv ) ratio on intracellular localization in ceria nanoparticles internalized by human cells' by Daniela Ferraro, et al., Nanoscale, 2017, 9, 1527–1538.